The imperfect-common-knowledge Phillips curve: Calvo versus Rotemberg - Radek Šauer (Deutsche Bundesbank, 2016)
I derive the imperfect-common-knowledge Phillips curve under the assumption of Rotemberg pricing. The curve differs from the Calvo version in one important aspect. Expectations of future relative prices impact in ation.
Keywords: D83; E31; 330; Phillips Curve; Rotemberg; Imperfect Knowledge